PELATIHAN PENERAPAN STRATEGI BELAJAR “MENGGUNAKAN OTAK” UNTUK PENINGKATAN KEMAMPUAN DAN PRESTASI BELAJAR SISWA SEKOLAH LANJUTAN TINGKAT PERTAMA - Hendrikus Masang Ban Bolly; Renny Sulelino (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract The human brain has an infinite capacity to collect the latest information, including building sub-systems in learning. The learning process will activate and involve the work of the brain in the learning and memory processes. Understanding how the brain works and the various supporting conditions that support the learning process can be the key to successful learning. Training on the Application of Learning Strategies "Using the Brain" to Improve Students' Learning Ability and Achievement at SLTP Negeri 3 Jayapura aims to provide insight and description to junior high school students on how learning strategies are based on understanding brain performance so that in the end they can improve students' learning abilities and achievements. This training was attended by 30 junior high school students in grades 7, 8, and 9. The training materials provided were the introduction of brain anatomy which plays an important role in the learning process, understanding memory performance, nutrition for the brain, training the brain to think, exercise and exercise for the brain, brain activation to understand, and music for the learner's brain. The training method is carried out directly through interactions in the form of delivering training materials, role-playing, games, and small group practice. The Learning Strategy Using the Brain Module product for junior high school students in the Covid-19 Pandemic Era has also obtained a Copyright letter from the Ministry of Law and Human Rights of the Republic of Indonesia. Pre and post test results showed an increase in students' knowledge of training materials, also showing good seriousness and focus during training. Abstrak Otak manusia memiliki kapasitas tak terhingga untuk mengumpulkan berbagai informasi terbaru, termasuk membangun sub-sistem dalam belajar. Proses belajar akan mengaktivasi dan melibatkan kerja otak dalam proses pembelajaran dan memori. Memahami bagaimana kinerja otak dan berbagai kondisi penunjang yang mendukung dalam proses belajar dapat menjadi kunci keberhasilan belajar. Pelatihan Penerapan Strategi Belajar “Menggunakan Otak” Untuk Peningkatan Kemampuan dan Prestasi Belajar Siswa di SLTP Negeri 3 Jayapura bertujuan untuk memberikan wawasan dan gambaran kepada siswa SLTP tentang bagaimana strategi pembelajaran berbasis pemahaman kinerja otak sehingga pada akhirnya mampu meningkatkan kemampuan dan prestasi belajar siswa. Pelatihan ini diikuti oleh 30 siswa SLTP kelas 7, 8 dan 9. Materi pelatihan yang diberikan yaitu pengenalan anatomi otak yang berperan penting dalam proses belajar, memahami kinerja memori, nutrisi untuk otak, melatih otak berpikir, senam dan olahraga untuk otak, aktivasi otak untuk memahami dan musik untuk otak pembelajar. Metode pelatihan dilakukan secara langung melalui interaksi berbentuk penyampaian materi pelatihan, bermain peran, permainan dan praktik kelompok kecil. Produk Modul Strategi Belajar Menggunakan Otak untuk siswa SLTP di Era Pandemik Covid-19 juga telah memperoleh surat Hak Cipta dari Kemukumham Republik Indonesia. Hasil pre dan post test menunjukkan terjadi peningkatan pengetahuan siswa terkait materi pelatihan, juga menunjukkan keseriusan dan fokus siswa yang baik selama pelatihan.